2016
DOI: 10.1016/j.renene.2016.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Exergy and exergoeconomic assessments of an electricity production system in a running wastewater treatment plant

Abstract: a b s t r a c tThis study aims at presenting a detailed exergy and exergoeconomic analyses of a biogas engine powered electricity production system in a wastewater treatment plant located in Adana, Turkey. The overall system consists of a compressor, a turbine, a pump, four heat exchangers and a gas engine. The effect of the each system component on the exergy efficiency and exergoeconomic parameters is analyzed separately. The analysis indicates that major exergy destruction happens in the gas engine as 4055.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The authors obtained overall energy and exergy efficiencies as 63.6% and 40%, respectively. Ozdil et al [33] conducted a detailed exergy and exergoeconomic analyses of a biogas powered electricity production in a WWTP. The authors found that the highest exergy destruction is obtained in the gas engine and an overall efficiency of 69.1%.…”
Section: Introductionmentioning
confidence: 99%
“…The authors obtained overall energy and exergy efficiencies as 63.6% and 40%, respectively. Ozdil et al [33] conducted a detailed exergy and exergoeconomic analyses of a biogas powered electricity production in a WWTP. The authors found that the highest exergy destruction is obtained in the gas engine and an overall efficiency of 69.1%.…”
Section: Introductionmentioning
confidence: 99%
“…The outputs illustrated that the gas engine and exhaust gas heat exchanger had been had the highest rate of exergy destruction in the proposed system, respectively. Also, the total cost of the system was founded 28.64 US$/h, and the exergy cost and electricity production cost in the turbine were founded 4.87 US$/h and 11.32 US$/GJ [5]. Performance analyses of multi-effect desalination coupled to a combined cooling, heating and power energy system were accomplished.…”
Section: Introductionmentioning
confidence: 99%